Shaped versus Round Implants for Breast Reconstruction: Indications and Outcomes - Nahabedian, Maurice Y. (Wolters Kluwer Health, 2014)
BACKGROUND: With the reintroduction of shaped silicone gel implants in the United States, questions regarding indications and outcomes for each are likely. The purpose of this article is to review the author’s early experience using shaped and round implants for breast reconstruction over a 14-month consecutive interval. METHODS: Breast reconstruction using shaped or round implants was performed on 69 women that included shaped silicone gel devices in 49 and round devices in 20. Patients were evaluated based on nipple-sparing vs skin-sparing mastectomy, 1-stage vs 2-stage, radiation therapy, unilateral vs bilateral, occurrence of complications, and follow-up. RESULTS: Of the 49 patients (78 breasts) who had shaped implants, reoperation was necessary in 6 patients (12.2%) and in 7 breasts (9%). This was secondary to infection in 2 breasts, capsular contracture in 2 breasts, incisional dehiscence in 1 breast, asymmetry in 1 breast, and exposure in 1 breast. Of the 20 patients (28 breasts) who had round implants, reoperation was necessary in 2 patients (10%) and 2 breasts (7.1%) and included the removal of the device secondary to a late infection in 1 patient and the correction of a malposition (double bubble deformity) in 1 patient. There were no malpositions involving the shaped silicone gel implants. CONCLUSIONS: Both shaped and round silicone gel devices can result in natural aesthetic outcomes. Shaped devices are preferred for contouring the upper pole and for optimizing breast projection. Round devices are preferred when the upper pole is not deficient and the patient desires softer breasts. Longer follow-up studies will be necessary.